International information policy: UNESCO in historical perspective - Julia Pohle (Research Handbook on Information Policy, 2021)
This chapter provides a short history of UNESCO's activities relating to information policy. It focuses on the political dynamics and debates surrounding the creation of UNESCO's two intergovernmental programmes explicitly dedicated to information: the General Information Programme (PGI), created in 1977, and the Information For All Programme (IFAP), which replaced the former in 2001. Both creation processes took place against the backdrop of highly politicized debates about information being a public resource or a commodity and the question of bridging the gap between industrialized and developing countries. The research is based on the analysis of archival records, interviews, policy texts and secondary literature, and seeks to situate UNESCO's efforts related to the formulation of national and international information policies in the institutional as well as the political contexts. It thus contributes to a better understanding of past and present policy debates about the value of information and global inequalities.
Keywords: 320; UNESCO; information policy; UNISIST; Information For All; information society; information economy